Sentinel lymph node biopsy omission in early-stage breast cancer: current evidence and clinical practice - Huang, Tao; Wang, Wenkang; Sun, Xianfu (Frontiers in Oncology, 2025)
Recent trials (e.g., SOUND, INSEMA) indicate that omitting SLNB in patients with small tumors, negative imaging, and favorable prognoses maintains outcomes, reduces complications, and improves quality of life (3,4). Specifically, the INSEMA trial demonstrated that patients who omitted SLNB experienced significantly lower rates of persistent lymphedema (1.8% vs. 5.7%), restriction of arm/shoulder mobility (2.0% vs. 3.5%), and pain with arm/shoulder movement (2.0% vs. 4.2%) compared to those undergoing SLNB. Consequently, guidelines now suggest omitting routine SLNB in elderly patients and those with very low-risk tumors(2). This review summarizes current evidence, eligible populations, theoretical rationale, controversies, and future directions regarding SLNB omission in early breast cancer management.